2010
DOI: 10.1111/j.1476-4431.2010.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study: The association of blood lactate concentration with outcome in dogs with idiopathic immune‐mediated hemolytic anemia: 173 cases (2003–2006)

Abstract: Lactate concentration at presentation was significantly higher in nonsurvivors than survivors. Lactate was significantly correlated with previously reported outcome variables but lactate concentration at admission, as a predictor for outcome was less than optimal. However, serial lactate concentration measurements may be more predictive as patients with persistent hyperlactatemia 6 hours after admission were less likely to survive. Prospective studies evaluating serial lactate concentration while controlling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 37 publications
3
64
0
Order By: Relevance
“…This parameter may be more relevant in dogs with pyometra that is medically treated. Although several authors reported that serum lactate may be used for the prognosis, diagnosis and assessment of treatment response in critically ill patients, especially when serial measurements are taken (Lagutchik et al, 1996;Nel et al, 2004;Koliski et al, 2005;Stevenson et al, 2007;Rabelo et al, 2009;Holahan et al, 2010), in this study preoperative hyperlactatemia was not significantly associated with morbidity and / or mortality (P=0.93), and no significant difference in pre-and postoperative blood lactate levels was found between groups G1 and G2 (P=0.35 and P=0.33). Hagman et al (2009) also found no significant correlation between hyperlactatemia and prognosis of this disease, and when cases of pyometra were compared with healthy dogs, the lactate concentrations were similar.…”
Section: Resultsmentioning
confidence: 99%
“…This parameter may be more relevant in dogs with pyometra that is medically treated. Although several authors reported that serum lactate may be used for the prognosis, diagnosis and assessment of treatment response in critically ill patients, especially when serial measurements are taken (Lagutchik et al, 1996;Nel et al, 2004;Koliski et al, 2005;Stevenson et al, 2007;Rabelo et al, 2009;Holahan et al, 2010), in this study preoperative hyperlactatemia was not significantly associated with morbidity and / or mortality (P=0.93), and no significant difference in pre-and postoperative blood lactate levels was found between groups G1 and G2 (P=0.35 and P=0.33). Hagman et al (2009) also found no significant correlation between hyperlactatemia and prognosis of this disease, and when cases of pyometra were compared with healthy dogs, the lactate concentrations were similar.…”
Section: Resultsmentioning
confidence: 99%
“…PS was used to calculate sample size for a hypothetical randomized controlled trial of a new treatment that would lead to 50% less mortality in dogs with IMHA with a mortality risk of 50%. (McManus et al 2001;Piek et al 2008Piek et al , 2011Holahan et al 2010). It may be unrealistic to expect a single therapy to be effective in these virtually moribund patients.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of severe anaemia may be another factor to consider. A study of dogs with IMHA demonstrated that the duration of hyperlactaemia was associated with a poor survival, which provides indirect evidence for the impact of anaemia since lactate concentrations are inversely correlated with the haematocrit (Holahan et al 2010). The effect of hypoxia may be difficult to identify since blood transfusions are a standard component of palliative therapy in IMHA.…”
Section: Risk Factors For Mortalitymentioning
confidence: 99%
“…Because of this, potential biomarkers for shock such as circulating lactate concentration have been investigated. 9 Several studies [10][11][12][13][14][15] in dogs have indicated that those with higher blood lactate concentrations at admission or persistent hyperlactatemia may have a worse outcome than those with lower lactate concentrations or in which lactate concentration becomes normalized. Lactate is metabolized back to pyruvate through the Cori cycle in the liver and to a lesser extent by the kidneys.…”
mentioning
confidence: 99%